The Application of Empiricism in Psychological Guidance Models (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2026)
The psychological guidance model plays a role in developing students' character and tolerance towards diversity in culture, religion, and social background. This approach is supported by Gordon Allport's trait theory and social interaction model that emphasizes learning through empirical experience to create an inclusive educational environment. This research aims to analyze the application of empiricism philosophy as the foundation of Gordon Allport's trait theory in the psychological guidance model. The method used is a qualitative literature study with content analysis of the literature. The results showed that: (1) Locke's tabula rasa and Hume's bundle of perceptions empiricism philosophy asserts that knowledge and personality are formed through empirical experience; (2) experiential-based interventions are effective in developing students' empathy and tolerance; (3) The integration of empiricism philosophy into the psychological guidance model results in a structured and evidence-based approach that is adaptive to individual needs in the context of inclusive education. (4) The psychological guidance model based on the philosophy of empiricism produces a scientific model with practical implications for the development of tolerance.